2002
DOI: 10.1051/0004-6361:20011579
|View full text |Cite
|
Sign up to set email alerts
|

A 327 MHz VLBI study of high redshift radio galaxies 1345+245, 1809+407 and 2349+289

Abstract: Abstract. Three high redshift radio galaxies, 1345+245 (4C 24.28, z = 2.889), 1809+407 (4C 40.36, z = 2.267) and 2349+289 (4C 28.58, z = 2.905) were observed with VLBI at 327 MHz giving an angular resolution of 40-100 mas and yielding images with the off-source noise level of 3σ 3.5 mJy/beam. On the centiarcsecond scale, the three sources are each characterized by two components with asymmetry both in flux density and in size. The compact components in the VLBI maps correspond to the hot spots in the VLA maps.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Our estimates of the magnetic field in those components are in good agreement with magnetic field estimates for other HzRGs (e.g. Cai et al 2002), and significantly higher than estimates found in typical nearby powerful radio galaxies (e.g. B ∼ 3 × 10 −4 for Cygnus A: Carilli & Barthel 1996).…”
Section: R E S U Lt S a N D Discussionsupporting
confidence: 89%
“…Our estimates of the magnetic field in those components are in good agreement with magnetic field estimates for other HzRGs (e.g. Cai et al 2002), and significantly higher than estimates found in typical nearby powerful radio galaxies (e.g. B ∼ 3 × 10 −4 for Cygnus A: Carilli & Barthel 1996).…”
Section: R E S U Lt S a N D Discussionsupporting
confidence: 89%
“…In general, the vast majority of the very long baseline interferometry (VLBI) experiments have been carried out mostly at 1.4 GHz or higher frequencies, where compact and flat‐spectrum radio sources clearly shine, and the telescope availability and performance are at their best. Some VLBI studies at 327 MHz have been published (e.g., Cai et al 2002; Lenc et al 2008). However, the poor quality of the images did not allow us to carry out accurate studies of the physics in the radio sources which were detected.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, although several hundred 90 cm VLBI observations have been made over the past two decades, images of only a few tens of sources have been published e.g. Altschuler et al (1995); Lazio & Cordes (1998); Chuprikov et al (1999); Cai et al (2002). With such a small sample it is difficult to quantify the total population and nature of these sources.…”
Section: Introductionmentioning
confidence: 99%